ISDC Review of 12 Initiative Proposals - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
Prepared for the 15th meeting of System Council held on March 8-9, 2022, this report proposes an external review of the second set of 12 CGIAR Initiatives proposals.